Compromised thermal tolerance of cardiovascular capacity in upstream migrating Arctic char and brown trout—are hot summers threatening migrating salmonids? - Mottola, Giovanna; Kristensen, Torstein; Anttila, Katja (Conservation Physiology, 2020)
publishedVersion